2012
DOI: 10.1289/ehp.1104139
|View full text |Cite|
|
Sign up to set email alerts
|

Variability of Urinary Phthalate Metabolite and Bisphenol A Concentrations before and during Pregnancy

Abstract: Background: Gestational phthalate and bisphenol A (BPA) exposure may increase the risk of adverse maternal/child health outcomes, but there are few data on the variability of urinary biomarkers before and during pregnancy.Objective: We characterized the variability of urinary phthalate metabolite and BPA concentrations before and during pregnancy and the ability of a single spot urine sample to classify average gestational exposure.Methods: We collected 1,001 urine samples before and during pregnancy from 137 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
221
9
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(274 citation statements)
references
References 34 publications
39
221
9
5
Order By: Relevance
“…Several studies have reported urinary levels of BPA (Becker et al 2009, Casas et al 2011, Braun et al 2012, Kasper-Sonnenberg et al 2012b, Koch et al 2012, Philippat et al 2012, Frederiksen et al 2013a, 2013b, Lassen et al 2013. Nearly all studies, including different subgroups of populations from both Europe and the USA, reported urinary BPA levels of a similar order of magnitude as observed in our studies.…”
Section: Non-persistent Environmental Chemicals In Danessupporting
confidence: 84%
See 2 more Smart Citations
“…Several studies have reported urinary levels of BPA (Becker et al 2009, Casas et al 2011, Braun et al 2012, Kasper-Sonnenberg et al 2012b, Koch et al 2012, Philippat et al 2012, Frederiksen et al 2013a, 2013b, Lassen et al 2013. Nearly all studies, including different subgroups of populations from both Europe and the USA, reported urinary BPA levels of a similar order of magnitude as observed in our studies.…”
Section: Non-persistent Environmental Chemicals In Danessupporting
confidence: 84%
“…In general, levels of MiBP among pregnant women in Europe were higher than in countries outside Europe (Tefre de Renzy-Martin et al 2014) including non-pregnant women in the USA (CDC 2012). All other common phthalate metabolites (MEP, MBzP, SDEHPm, and SDiNPm) were observed at lower levels in Danish pregnant women than in other biomonitoring studies of pregnant women (Braun et al 2012, Tefre de RenzyMartin et al 2014. However, estimated daily exposure levels to the common phthalates and most of the other non-persistent chemicals in Danish pregnant women were similar to levels observed in non-pregnant Danish women (Frederiksen et al 2013b, Tefre de Renzy-Martin et al 2014.…”
Section: Non-persistent Environmental Chemicals In Danesmentioning
confidence: 80%
See 1 more Smart Citation
“…These in utero effects are likely to also occur in BPA exposed human males. Such evidence has been derived from a recent epidemiological study conducted by Braun et al ( 2012 ), who detected BPA in urine samples of pregnant women, suggesting gestational exposure. Moreover, Miao et al ( 2011a ) demonstrated an association between parental occupational BPA exposure during pregnancy and shortened AGD in male offspring.…”
Section: Effects Of In Utero Exposure To Bisphenol a On Male Reproducmentioning
confidence: 91%
“…They threaten intensely reproductive health of human and wildlifes, resulting in the reduction of testosterone level, sperm production and fertility, and change other reproductive parameters (Fisher et al, 2003;Han et al, 2004;Herath et al, 2004;Li et al, 2010). It has been addressed that there is necessity to be evaluated the exposure risks of single or mixture of two or more endocrine disrupters to human and animal health (Tinwell and Ashby, 2004;Brian et al, 2005;Li et al, 2010;Braun et al, 2012).…”
Section: Discussionmentioning
confidence: 99%